Descriptive review of current practices and prognostic factors in patients with ovarian cancer treated by pressurized intraperitoneal aerosol chemotherapy (PIPAC): a multicentric, retrospective, cohort of 234 patients - Kefleyesus, Amaniel; Bhatt, Aditi; Escayola, Cecilia; Khomyakov, Vladimir; Hübner, Martin; Reymond, Marc A.; Thieme, René; Sgarbura, Olivia; Willaert, Wouter; Ceelen, Wim; Di Giorgio, Andrea; Vizzielli, Giuseppe; et al. (Frontiers in Oncology, 2023)
Introduction: Ovarian cancer (OC) is the primary cause of mortality in women diagnosed with gynecological cancer. Our study assessed pressurized intraperitoneal aerosol chemotherapy (PIPAC) as treatment for peritoneal surface metastases (PSM) from recurrent or progressive OC and conducted survival analyses to identify prognostic factors. Material and methods: This retrospective cohort study, conducted across 18 international centers, analyzed the clinical practices of patients receiving palliative treatment for PSM from OC who underwent PIPAC. All patients were initially treated appropriately outside any clinical trial setting. Feasibility, safety, and morbidity were evaluated along with objective endpoints of oncological response. Multivariate analysis identified prognostic factors for OS and PFS. Results: From 2015-2020, 234 consecutive patients were studied, from which 192 patients were included and stratified by platinum sensitivity for analysis. Patients with early recurrence, within one postoperative month, were excluded. Baseline characteristics were similar between the groups regarding platinum sensitivity (platinum-sensitive (PS) and resistant (PR)), but chemotherapy frequency differed, as did PCI before PIPAC. Median PCI decreased in both groups after three cycles of PIPAC (PS 16 vs. 12, p < 0.001; PR 24 vs. 20, p = 0.009). Overall morbidity was 22%, with few severe complications (4-8%) or mortality (0-3%). Higher pathological response and longer OS (22 vs. 11m, p = 0.012) and PFS (12 vs. 7m, p = 0.033) were observed in the PS group. Multivariate analysis (OS/PFS) identified ascites (HR 4.02, p < 0.001 / 5.22, p < 0.001), positive cytology at first PIPAC (HR 3.91, p = 0.002 / 1.96, p = 0.035), and ≥ 3 PIPACs (HR 0.30, p = 0.002 / 0.48, p = 0.017) as independent prognostic factors of overall survival/progression-free survival. Conclusions: With low morbidity and mortality rates, PIPAC is a safe option for palliative treatment of advanced ovarian cancer. Promising results were observed after 3 PIPAC, which did improve the peritoneal burden. However, further research is needed to evaluate the potential role of PIPAC as an independent prognostic factor.